Let Us Celebrate 20 Years of Struggle! - Jalandoni, Luis (Kasarinlan: Philippine Journal of Third World Studies; Vol 8 No 4 (1993): The NDF at 20: A Front United?)
A speech delivered at the 20th National Democratic Front (NDF) anniversary celebration in Brussels, Belgium, April 23, 1993.